2020
DOI: 10.1515/nanoph-2020-0357
|View full text |Cite
|
Sign up to set email alerts
|

A fiber optic–nanophotonic approach to the detection of antibodies and viral particles of COVID-19

Abstract: Dr. Deborah Birx, the White House Coronavirus Task Force coordinator, told NBC News on “Meet the Press” that “[T]he U.S. needs a ‘breakthrough’ in coronavirus testing to help screen Americans and get a more accurate picture of the virus’ spread.” We have been involved with biopathogen detection since the 2001 anthrax attacks and were the first to detect anthrax in real-time. A variation on the laser spectroscopic techniques we developed for the rapid detection of anthrax can be applied to detect the Severe Acu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Many approaches were proposed for detecting the virus in infected people including different tests and sensors. Various biosensors for detecting COVID-19 were reported which indicated interesting results [ 2 , 3 ]. The optical biosensors can diagnose the COVID-19 very fast and with precise results.…”
Section: Introductionmentioning
confidence: 99%
“…Many approaches were proposed for detecting the virus in infected people including different tests and sensors. Various biosensors for detecting COVID-19 were reported which indicated interesting results [ 2 , 3 ]. The optical biosensors can diagnose the COVID-19 very fast and with precise results.…”
Section: Introductionmentioning
confidence: 99%
“…The coronavirus macromolecules are of spherical shape of 100-140 nm in diameter, with an outer envelope bearing 20 nm-long club-shaped spike proteins [43]; in the visible wavelength range, their refractive index is 1.06, and they are optically anisotropic (the scattering indicatrix is polarization-dependent) [43]. Recent studies related to coronavirus identification in the blood have shown the possibility of various approaches to their investigation [44][45][46], among which the optical methods can be distinguished, including the fluorescence-based methods, employment of surface plasmons, plasmon-enhanced fluorescence, surface-enhancing Raman scattering, colorimetric biosensor methods [44,45], and approaches of fiber optics in the nanophotonic framework [46]. Such optical approaches enable detection of the immunoglobulin M and G antibodies or the SARS-CoV-2 molecules themselves.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that using highly stable UCNPs could improve the limit of detection (LOD) of upconversion-linked immunosorbent assay (ULISA) by an order of magnitude compared to commercially available assays 30 , 31 . More sensitive optical readout can also improve the LOD in such bioassays 32 , 33 . These progressions toward single molecule detection are pushing the sensitivity, specificity, and LOD beyond what was once theoretically possible 34 36 .…”
Section: Introductionmentioning
confidence: 99%